The Influence of Self-Compassion and Mindfulness on Nurses’ Caring Behavior - Lia Winarti; Rokiah Kusumapradja; Idrus Jusat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Caring behavior is the core of high-quality nursing services. In practice, it is influenced by various psychological factors and work-related stress. Self-compassion and mindfulness are believed to help nurses maintain emotional balance in delivering empathetic and humane nursing care. This study aims to analyze the effect of self-compassion and mindfulness on nurses’ caring behavior, with work stress as a mediating variable. A quantitative approach with a cross-sectional design was used. Descriptive analysis employed the Three Box Method, while inferential analysis used SEM-PLS. The study population consisted of all nurses at Cilincing District General Hospital (N = 113), using total sampling. The results of the study indicate that the proposed model is considered fit (p = 0.133) and appropriate for testing the influence of self-compassion and mindfulness on caring behavior, with work stress as a mediating variable. Self-compassion has a significant positive effect on caring behavior (p = 0.000), while mindfulness does not have a direct effect (p = 0.891), but shows a significant indirect effect through the reduction of work stress (p = 0.044). Both self-compassion (p = 0.029) and mindfulness (p = 0.000) negatively affect work stress. Interestingly, work stress positively influences caring behavior (p = 0.030). To enhance the influence of self-compassion and mindfulness on caring behavior, hospitals should develop psychological intervention programs based on self-compassion and mindfulness to help nurses manage stress and strengthen caring practices. A systemic approach that considers organizational factors is also necessary to support the consistent implementation of caring behavior.